2002
DOI: 10.1103/physrevlett.88.034102
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Induced Resonance in Delayed Feedback Systems

Abstract: We study the influence of noise in the dynamics of a laser with optical feedback. For appropriate choices of the feedback parameters, several attractors coexist, and large enough noise induces jumps among the attractors. Based on the residence times probability density, it is shown that with increasing noise the dynamics of attractor jumping exhibits a resonant behavior, which is due to the interplay of noise and delayed feedback. It is also shown that this type of resonance is not specific to the model equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(118 citation statements)
references
References 32 publications
3
115
0
Order By: Relevance
“…It is thus an indication of the constructive influence of noise in nonlinear systems (García-Ojalvo & Sancho 1999;Masoller 2002;Linder et al 2004;Hizanidis et al 2006;Sagués et al 2007). Most of the work on stochastic excitable systems assumes the stochastic input to be uncorrelated white noise.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus an indication of the constructive influence of noise in nonlinear systems (García-Ojalvo & Sancho 1999;Masoller 2002;Linder et al 2004;Hizanidis et al 2006;Sagués et al 2007). Most of the work on stochastic excitable systems assumes the stochastic input to be uncorrelated white noise.…”
Section: Introductionmentioning
confidence: 99%
“…Stochastic resonance has been studied in variety of fields [11,12,13,14,15]. In particular, we have proposed a variation of stochastic resonance, called delayed stochastic resonance, which arises from a combination of noise with delayed dynamics [16,17,18]. We can infer from such an effect that a similar resonance behavior could be found in fluctuations in predictive dynamics.…”
Section: Model and Analysismentioning
confidence: 83%
“…Previous studies of a SCL subject to FOF demonstrated that noise influences the dynamics substantially [21,23].…”
Section: Influence Of Noisementioning
confidence: 99%
“…Other studies have shown that noise induces jumps between stable attractors if the ratio of the noise strength to potential barrier is large enough [23]. A good understanding of this behavior is gained via an examination of the time-series 195 in conjunction with the phase-portraits and rf spectra.…”
mentioning
confidence: 99%